Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) Produk Olahan di Desa Antibar dalam Perspektif Ekonomi Lokal Implementasi Model Bisnis Berkelanjutan untuk Produk Olahan Hasil Alam di Desa Antibar: Studi Kasus Dusun Permai - Prasetyo, Wisnu; Marumpe, Dody Pratama; Fitonia, Blessita Putri; Syari, Nadia Ukti; Rahmaniar, Desi; Aprija, Een (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service activity is based on the problem of the lack of public knowledge regarding the processing and marketing of new products from abundant natural resources in their area and the lack of public knowledge for business development in the current era. Product processing and marketing is one of the activities that plays an important role in the development of the natural resource-based economic sector. With good processing and effective marketing strategies, natural products can compete in domestic and international markets, while improving the welfare of farmers and natural resource managers. This activity aims to increase public awareness that abundant natural products have high value if they are processed first into new products and provide an effective way to market their products in order to increase sales. The approach methods applied are socialization, training in making processed products from natural products, and assistance in marketing digital-based products. The results of this activity are expected to increase public awareness to process natural products into new products and can increase new product processing entrepreneurs from natural products, as well as increase public understanding in marketing more modern products to increase sales.